Interaction of the Joining Region in Junctophilin-2 With the L-Type Ca2+ Channel Is Pivotal for Cardiac Dyad Assembly and Intracellular Ca2+ Dynamics. Issue 1 (8th January 2021) - Gross, Polina; Johnson, Jaslyn; Romero, Carlos M.; Eaton, Deborah M.; Poulet, Claire; Sanchez-Alonso, Jose; Lucarelli, Carla; Ross, Jean; Gibb, Andrew A.; Garbincius, Joanne F.; Lambert, Jonathan; Varol, Erdem; et al.
Abstract : Rationale: Ca 2+ -induced Ca 2+ release (CICR) in normal hearts requires close approximation of L-type calcium channels (LTCCs) within the transverse tubules (T-tubules) and RyR (ryanodine receptors) within the junctional sarcoplasmic reticulum. CICR is disrupted in cardiac hypertrophy and heart failure, which is associated with loss of T-tubules and disruption of cardiac dyads. In these conditions, LTCCs are redistributed from the T-tubules to disrupt CICR. The molecular mechanism responsible for LTCCs recruitment to and from the T-tubules is not well known. JPH (junctophilin) 2 enables close association between T-tubules and the junctional sarcoplasmic reticulum to ensure efficient CICR. JPH2 has a so-called joining region that is located near domains that interact with T-tubular plasma membrane, where LTCCs are housed. The idea that this joining region directly interacts with LTCCs and contributes to LTCC recruitment to T-tubules is unknown. Objective: To determine if the joining region in JPH2 recruits LTCCs to T-tubules through direct molecular interaction in cardiomyocytes to enable efficient CICR. Methods and Results: Modified abundance of JPH2 and redistribution of LTCC were studied in left ventricular hypertrophy in vivo and in cultured adult feline and rat ventricular myocytes. Protein-protein interaction studies showed that the joining region in JPH2 interacts with LTCC-α1C subunit and causes LTCCs distribution to the dyads, where they colocalize with RyRs. A JPH2 with induced mutations in the joining region (mut PG1 JPH2) caused T-tubule remodeling and dyad loss, showing that an interaction between LTCC and JPH2 is crucial for T-tubule stabilization. mut PG1 JPH2 caused asynchronous Ca 2+ -release with impaired excitation-contraction coupling after β-adrenergic stimulation. The disturbed Ca 2+ regulation in mut PG1 JPH2 overexpressing myocytes caused calcium/calmodulin-dependent kinase II activation and altered myocyte bioenergetics. Conclusions: The interaction between LTCC and the joining region in JPH2 facilitates dyad assembly and maintains normal CICR in cardiomyocytes. Abstract : Supplemental Digital Content is available in the text.